Drilling practice Zhongzihao gas exploration well in the thrust belt of the western margin - Wang Hao; Wei Yan (E3S Web of Conferences, 2022)
The geological structure of Zhong-7 well and Zhong-14 well is the Hengshanpu section of the thrust belt in the western margin of the Ordos Basin, and there have been few construction wells in this area in the past two years. During the construction of the two wells, the formation stability of the entire well section was extremely poor, especially Shiqianfeng. The following strata collapsed seriously and frequently encountered blockages during tripping. During the construction, measures such as optimizing the system, enhancing plugging, improving suppression, wall patching in complex well sections, and fiber cleaning were adopted to obtain valuable experience for the later construction of the Zhongzi gas exploration well in the thrust belt of the western margin.